DIMENSIONS OF CULINARY TOURISM AND HOSPITALITY IN GOLDEN TRIANGLE OF INDIA - Rekha MAITRA; Tarun BANSAL; Ansted Iype JOSEPH (Studia Universitatis Babeş-Bolyai Negotia, 2021)
Purpose: Delhi, Agra and Jaipur form the golden triangle of India. This tourist triangle is designed to up-sell in the market with lucrative offers. “Palace on Wheels” is a luxury train that runs on this route and is targeted for foreign clientele with its extravagance segment. These three destinations have their significance due to the presence of historical monuments and UNESCO world heritage sites i.e., Qutub Minar, India Gate, Tajmahal, and many more. These places also offer an enormous variety of food and beverage with warm hospitality to relieve the tired tourists. The gourmet dishes of Golden Triangle are a must to try as it dates to the traditional cooking combined with a spicy aroma and soothing beverages. The paper is structured to judge the culinary facet and warm hospitality of the Golden Triangle. The main objective is to find out the impact of traditional food in attracting travellers. It will also identify the food trail experiences in enhancing a niche segment of buyers for culinary tourism. Design/methodology/approach: The research is exploratory and draws on food and beverage culinary experience delivery in the Golden Triangle. The exploratory research will judge the effectiveness of food tours and the warm hospitality extended to food tourists. Findings: The research will examine how Culinary Tourism and Hospitality in the Golden Triangle of India can form a niche segment of food and beverage buyers. How it enhances the customer experience with hospitable conduct. The study will highlight the benefits of culinary tourism and hospitality. Practical implications: The paper recommends the concepts of food and beverage culinary tourism experience for creating a niche segment of buyers as well as attracting potential buyers with its approach. The research will synthesize the factors to improve customer interest in taking food and beverage tourism. Originality/value: The research sought to address the advantages of curating food and beverage tourists in the golden triangle of India. It will also address how food and beverage tours can influence culinary tourism.